The effectiveness of e-learning in light of the Corona pandemic from the perspective of Tikrit University students (Eurasian Journal of Media and Communications, 2024)
The research problem lies in answering the following questions: -How effective and sustainable is e-learning in light of the spread of the Corona virus, from the point of view of Tikrit University students ? -What is the level of obstacles to using e-learning at Tikrit University? The research aims to reveal: -The effectiveness of e-learning in light of the spread of the Corona pandemic from the perspective of students from the College of Physical Education and Sports Sciences / Tikrit University. -Measuring the level of continuity of the e-learning process. The research community consists of students from Tikrit University/College of Physical Education and Sports Sciences for the academic year (2020-2021), as the size of the original community was (935) male and female students, distributed over four classes and for morning and evening studies. As for the research sample, it was chosen randomly. The number of students reached (240) male and female students, who were selected from four classes in the college. (60) male and female students were selected from each of the above classes, as shown in the table below.